Women's pattern of use at two recreational parks in Klang Valley, Malaysia - Khairrussalleh, Nadzirah; Hussain, Norhuzailin (Faculty of Design & Architecture, Universiti Putra Malaysia, 2017)
This paper examines how Malaysian women use the recreational parks in Klang Valley, Malaysia. Previous studies in Malaysia have shown that women are engaged less in leisure and recreational activities than men due to their family commitments and other constraints. The aim of this paper is to discuss concerning the visits in urban recreational parks and the related feelings by women park users. The objectives are to gather information on park users’ demographic backgrounds, and to identify the pattern of use and feelings related to the recreational parks by Malaysian women. The method used was self-administered questionnaire surveys where the total of 510 women park users were surveyed at two recreational parks in Klang Valley. Site observations were used to support the survey data. The results show that majority of the respondents prefer to visit the parks on weekend, usually with companions such as friends or/and family members. Most of the women mentioned having positive feelings while in the parks such as they were more relax and energetic after visiting the parks. The results may contribute and assist park managers, city planners and designers to design and having better management of parks for women users in the future.